1999
DOI: 10.1111/j.1528-1157.1999.tb00888.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Anticonvulsant and Psychoactive Drugs

Abstract: Summary: This review considers the relevance of pharmacokinetic interactions between antiepileptic drugs (AEDs) and psychoactive drugs in the treatment of mood disorders in patients with epilepsy. The determination of plasma levels of some of these drugs (mainly the AEDs) has enabled clinicians to evaluate the kinetic modifications during the course of such combined therapies and to adjusting the dosages in cases of subtherapeutic or toxic levels. In general, phenobarbital, phenytoin, and carbamazepine stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 54 publications
1
27
0
1
Order By: Relevance
“…Fluoxetine was found to be effective against maximal electroshock-induced tonic extension in rats (44), audiogen seizures in mice and rats (21,25), and focally evoked limbic motor seizures in rats (22). Several clinical observations and animal studies showed that fluoxetine enhanced the anticonvulsant potency of various antiepileptic drugs (19,20,(45)(46)(47). Regarding the effective anticonvulsant dose of the drug, fluoxetine exerted 50% protective effect at 5 mg/kg in the limbic motor seizure model, whereas, in the genetically epilepsy-prone rats (GEPR-9) the ED 50 was ~16 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoxetine was found to be effective against maximal electroshock-induced tonic extension in rats (44), audiogen seizures in mice and rats (21,25), and focally evoked limbic motor seizures in rats (22). Several clinical observations and animal studies showed that fluoxetine enhanced the anticonvulsant potency of various antiepileptic drugs (19,20,(45)(46)(47). Regarding the effective anticonvulsant dose of the drug, fluoxetine exerted 50% protective effect at 5 mg/kg in the limbic motor seizure model, whereas, in the genetically epilepsy-prone rats (GEPR-9) the ED 50 was ~16 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…The drug interactions between these two classes of agents focus on the cytochrome P450 enzymes. For example, the enzyme-inducing AEDs PB, PHT, and CBZ stimulate the metabolism of tricyclic antidepressants (TCAs), and the TCAs have an inhibitory effect on the metabolism of some AEDs (120), resulting in a reduction in the plasma concentration of TCAs, with a concomitant increase in the plasma concentration of the coadministered AED. Examples of TCAs that interact in this complex manner include nortryptiline, imipramine, nomifensine, and trazodone (121,122).…”
Section: Psychotropic Drugsmentioning
confidence: 99%
“…However, some clinically relevant interactions may occur by inhibition of CYP isoenzymes, especially when in a regimen of multiple drugs, which is the case of our patients 12 . Serotonin reuptake inhibitors can also cause an increase in plasma levels of AEDs through inhibition of P450 2D6 isoenzyme 13 . As the concomitant administration of AEDs and serotonin reuptake inhibitors is common, therapeutic drug monitoring may be useful in designing correct and rational therapy, but further studies are necessary 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin reuptake inhibitors can also cause an increase in plasma levels of AEDs through inhibition of P450 2D6 isoenzyme 13 . As the concomitant administration of AEDs and serotonin reuptake inhibitors is common, therapeutic drug monitoring may be useful in designing correct and rational therapy, but further studies are necessary 13 . We can conclude by these data that patients with chronic neurological diseases, such as epilepsy and headaches, have a high number of comorbidities.…”
Section: Discussionmentioning
confidence: 99%